Volcanoes - Cassie Mayer (China Raintree Publisher, 2007)
Each book in this series begins by explaining what a landform is before launching into the specific type of landform covered in the book. The titles use a compare and contrast format in order to get readers understanding the main characteristics of the geography being discussed. Detailed photos and diagrams help drive home the Earth science topics covered. Through stunning photographs and simple text, the books in this series introduce landforms and their characteristics. In this book, children learn about the features of volcanoes, where volcanoes are found, and what makes volcanoes unique.
Keywords: Easy Read Nonfiction -- Easy Read Nonfiction